Early ovarian carcinomas - Heraud Griva, César (2015)
The author has reviewed the medical records of 260 women living with ovarian tumors, a total of 10,450 patients treated gynecological Loayza Hospital in Lima, between 1960 and 1969; of that number, 42 were for early ovarian carcinomas in its various clinical forms and anatomical and histological types.